Pelatihan Tentang Model Akumulasi Logam Berat Dalam Tubuh Organisme Pada Siswa Madrasah Aliyah Negeri 1 Kota Bima - Khairuddin Khairuddin; M. Yamin; Kusmiyati (Universitas Mataram, 2026)
The accumulation model of heavy metals Cadmium (Cd), mercury (Hg), and Lead (Pb) in humans is something that needs to be understood by students at various school levels including students of State Islamic Senior High School 1 (MAN 1) Bima City. The problem faced by partners is how efforts must be made to gain knowledge, and what skills must be possessed by students of MAN 1 Bima City in order to understand the accumulation model of heavy metals Cd, Hg, and Pb in the body of organisms in life. This training aims to provide an understanding of the accumulation model of heavy metals Cd, Hg, and Pb for students of MAN 1 Bima City. The benefit of this training is an increase in understanding of the accumulation model of heavy metals Cd, Hg, and Pb in everyday life. The methods used in this training include Lectures, Demonstrations, Questions and Answers and Discussions. The conclusion of the training is that the knowledge and skills about the accumulation of heavy metals Cd, Hg, and Pb in the bodies of organisms in students of MAN 1 Kota Bima have increased so that they can understand the accumulation model of heavy metals Cadmium, Mercury, and Lead in the bodies of organisms